SECULARISM IN THE SHADOW OF HINDUTVA: RELIGION AND THE 2019 AND 2024 INDIAN PARLIAMENTARY ELECTIONS - Djogatovic, Veljko (Serbian political thought, 2025)
This study explores the impact of Hindu nationalism on the concept of secularism in India, with a particular focus on the parliamentary elections held in 2019 and 2024. In the context of the growing social and political importance of Hindu nationalism, the author analyzes how this ideology influences the application and development of secular principles in political discourse and election campaigns, with a special focus on the two election cycles mentioned above. By analyzing the political and social narrative, election results, and election agenda, the study explores how Hindu nationalism shapes the political landscape and contributes to the development of religious and political polarization. Special attention is paid to the role of the Bharatiya Janata Party in promoting Hindu nationalism and its impact on the development of social and religious tensions. The research findings demonstrate the significant impact of Hindu nationalism on the erosion of the pillars of secularism and the intensification of polarization in Indian society. This study also provides significant insight into the dynamics of the relationship between religion and politics in contemporary India – a topic that has been almost completely neglected in domestic scholarship.